Retailer Insights on Amul’s Fresh Milk Products Supply Chain Study in Anand City and Vidyanagar, India - , Smit Trivedi; , M.D. Gurjar; , K.C. Kamani; , M.C. Prajapati; , A.K. Makwana (Archives of Current Research International, 2024)
This study investigates retailer insights within supply chain of Amul fresh milk products in Anand city and Vidyanagar. A cross-sectional study using semi- structured questionnaires for data collection and statistical tools for analysis. Spanning from 1st March to 7th June, 2024, the project is guided by specific objectives provided by AMUL Dairy. These objectives include studying the insights of retailer with in supply chain of fresh milk products. Data collection through semi-structured questionnaires distributed to 40 retailers random sampling methods. Analysis includes statistical tools like frequencies, percentages, and Likert scales to derive insights the positive aspects of fresh milk products supply chain in Anand city and Vidyanagar. Retailers express high levels of satisfaction with promotional materials, indicating effective marketing strategies and strong brand presence. These findings highlight the strengths of Amul's supply chain, demonstrating successful collaboration and high level of customer satisfaction among stakeholder. Additionally concludes with actionable recommendations for fresh milk products supply chain, but notes that the data may not be generalizable due to statistical insignificance.